Neurociência e educação infantil: para além da estimulação precoce - Mascarenhas, Tárcila Santos de Souza (Universidade Federal de São Carlos, 2017)
This scientific research is relevant for the development of intentional and quality pedagogical practices aimed at children from 0 to 3 years old. The contributions of neuroscience and the Cultural Historical Theory were the basis of this research and the research question that guided the study was the following: Neuroscience research can contribute to the improvement and quality of learning of children in Early Childhood Education in the range of 0 to 3 years? Based on this research question, we draw the following general objective: to develop a theoretical study on neuroscience research that focuses the teaching and learning issues in Early Childhood Education. The research is theoretical and was based on Marxist Historical-Dialectical Materialism and Vigotsky's Cultural Historical Theory. For the analysis of the data we used qualitative methods which allowed us to construct the final analyses. The results allow us to advance studies on child development, since it showed that the activity of stimulating children from their main activity can contribute to the potentiation of teaching and learning processes.
Neuroscience and early childish education: beyond the early stimulation
Keywords: Neurociência; Educação infantil; Teoria Histórico-Cultural; Estimulação precoce Infantil; Atividade Principal; Neuroscience; Early childhood education; Cultural historical theory; Early childhood stimulation; Main activity; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM